Non-psychiatrist prescriptions within the Brazilian National Health System represents a risk to patients in the use of psychotropic pharmacotherapies (Research, Society and Development, 2021)
This cross-sectional study collected data from the Brazilian National Health System (NHS) patients’ that filled their psychotropic prescriptions in NHS owned pharmacies. The study aimed to identify oversights in psychotropic prescriptions leading to insecure therapeutic. Patients in use of at least one psychotropic drug in 12 months were identified by a retrospective data search and considered for the study. After examining 15,001 patients in use of psychotropic medicines, 7,440 met the inclusion criterion. The majority of patients were women (67.1%), 54.2% of prescriptions analysed over the studied period presented multiple medicines including one psychotropic, and 54.7% cursing with psychotropic monotherapy. In 92.7% of cases, only one medicine was dispensed and prescriptions from psychiatrists represented only 17.6% of cases. In terms of safety, 9.5% of patients had at least one potential drug interaction of clinical significance, and 71.5% of elder patients had at least one drug that was potentially inappropriate for their age group use. These findings suggest urgency in integrating patients’ medical records information to pharmacotherapy history at the pharmacy computer technology applied for dispensing, reducing harm to patients in the use of psychotropic drugs.